Transparent Windows on Food Packaging Do Not Always Capture Attention and Increase Purchase Intention - Ma, Xueer; Zhuang, Xiangling; Ma, Guojie (Frontiers in Psychology, 2020)
Transparent windows on food packaging can effectively highlight the actual food inside. The present study examined whether food packaging with transparent windows (relative to packaging with food- and non-food graphic windows in the same position and of the same size) has more advantages in capturing consumer attention and determining consumers’ willingness to purchase. In this study, college students were asked to evaluate prepackaged foods presented on a computer screen, and their eye movements were recorded. The results showed salience effects for both packaging with transparent and food-graphic windows, which were also regulated by food category. Both transparent and graphic packaging gained more viewing time than the non-food graphic baseline condition for all the three selected products (i.e., nuts, preserved fruits and instant cereals). However, no significant difference was found between transparent and graphic window conditions. For preserved fruits, time to first fixations was shorter in transparent packaging than other conditions. For nuts, the willingness to purchase was higher in both transparent and graphic conditions than the baseline condition, while the packaging attractiveness played a key role in mediating consumers’ willingness to purchase. The implications for stakeholders and future research directions are discussed.